Pregnancy in Patients With AQP4-Ab, MOG-Ab, or Double-Negative Neuromyelitis Optica Disorder. (13th April 2021) - Collongues, Nicolas; Alves Do Rego, Cecilia; Bourre, Bertrand; Biotti, Damien; Marignier, Romain; da Silva, Ana Martins; Santos, Ernestina; Maillart, Elisabeth; Papeix, Caroline; Palace, Jacqueline; Leite, Maria Isabel S.; De Seze, Jerome
Abstract : Objective: To analyze the effects of pregnancy on neuromyelitis optica spectrum disorder (NMOSD) according to patients' serostatus and immunosuppressive therapy (IST). Methods: We performed a retrospective multicenter international study on patients with NMOSD. Patients were tested for aquaporin-4 (AQP4) and myelin oligodendrocyte glycoprotein (MOG) antibodies (Ab). Informative pregnancies were reported when NMOSD onset occurred before or during pregnancy or up to 12 months postpartum. The mean annualized relapse rate (ARR) was calculated for the 12 months before conception, for each trimester of pregnancy, and postpartum. Events such as miscarriage, abortion, and preeclampsia were reported. IST was considered if taken in the 3 months before or during pregnancy. Results: We included 89 pregnancies (46 with AQP4-Ab, 30 with MOG-Ab, and 13 without either Ab) in 58 patients with NMOSD. Compared to the prepregnancy period, the ARR was lower during pregnancy in each serostatus group and higher during the postpartum period in patients with AQP4-Ab ( p < 0.01). Forty-eight percent (n = 31) of pregnancies occurred during IST and these patients presented fewer relapses during pregnancy and the 12 months postpartum than untreated patients (26% vs 53%, p = 0.04). Miscarriages occurred in 10 (11%) pregnancies, and were mainly in patients with AQP4-Ab (with or without IST) and a previous history of miscarriage. Preeclampsia was reported in 2 (2%) patients who were AQP4-Ab-positive. Conclusion: We found a rebound in the ARR during the first postpartum trimester that was higher than the prepregnancy period only in AQP4-Ab-positive patients. Taking IST just before or during pregnancy reduces the risk of relapses in these conditions.